A new fatigue damage accumulation model considering loading history and loading sequence based on damage equivalence. (May 2018) - Si-Jian, Lin; Wei, Long; Da-Qing, Tian; Jun-Bi, Liao
In this study, a new nonlinear fatigue damage accumulation model is proposed to consider the effects of loading history and loading sequence under multi-level stress loading based on the Miner–Palmgren rule and S-N curve. By using damage equivalence, the new model is simplified and another form of the model is given. This model improves the application of the traditional Miner–Palmgren rule, by considering not only the loading sequence effect but also the loading history effect. The methods for calculating the degree of safety of specimens and cumulative damage of low-amplitude loads are also presented. Applicability of the new model is validated by predicting the fatigue life of 16Mn and 45 steel specimens under two-level stress loading. Further validation is carried out for the case of 41Cr4 and Aluminum alloys 6082 T6 under multi-level stress loading, and the strengthening and damaging effect of low-amplitude loads is considered. Comparing with the Miner–Palmgren rule and some new models, this new model gives more accurate and reliable prediction.